A Variability-Based Model to Support the Design of Public Crisis Information and Communication Systems - Dusse, Flavio; Pereira, Jorge; Novais, Renato; Vieira, Vaninha; Mendonça, Manoel (Proceedings of the International ISCRAM Conference, 2025)
A crisis is an inherently unpredictable event. However, it often exhibits patterns that can help authorities anticipate challenges and respond more effectively to crisis situations. Current information systems for public communication during crises tend to focus on disseminating standardized messages across various communication channels. This approach contradicts effective communication practices, as different audiences have different information needs. Inappropriate public communication messages can generate noise, amplify perception of risk, and increase feelings of insecurity. This paper proposes a novel model to guide the development of information systems for crisis communication. To ensure flexibility and adaptability across diverse crisis scenarios, our approach maps and models variability in the crisis communication process. This variability model enables the rapid creation of tailored yet consistent crisis communication, delivered through appropriate channels to meet the needs of different audiences - such as crisis responders, authorities, press and the general public - who are the intended recipients of the system.